Analysis of financial statements on the receipt of tax revenue at the DJP East Tangerang Pratama Tax Service Office for the period 2015-2021 - Muhammad Imam Reza; Herayati Herayati; Martinus Wahyu Purnomo (Junal Ilmu Manajemen, 2023)
Based on preliminary observations in the field, there appear to be several issues related to revenue receipts, and one of the identified problems is the significant fluctuation in tax revenue between periods. If this continues, tax revenue in this region will become a hindrance to the country's development. This research aims to compare the financial statements of the Tax Service Office of East Tangerang Primary Tax Office for the period 2015-2021 and identify the causes of fluctuation and obstacles in revenue collection. This research utilizes a descriptive quantitative method. Based on the research and analysis conducted by the researcher, it can be concluded that the highest revenue was recorded in the period 2015-2016, as economic changes had not occurred at that time. Economic changes started from the period 2018-2019 until the end of 2019-2021. These economic changes caused fluctuations during that period, which eventually hindered tax revenue collection at the Tax Service Office of East Tangerang Primary Tax Office. Another obstacle is the instability in one of the elements of tax revenue, which is caused by income gaps during certain periods.